Freedom from fear - Kennedy, David M. (Oxford University Press, 2001)
The Depression was both a disaster and an opportunity. As David Kennedy vividly demonstrates, the economic crisis of the 1930s was far more than a simple reaction to the alleged excesses of the 1920s. For more than a century before 1929, America's unbridled industrial revolution had gyrated through repeated boom and bust cycles, wastefully consuming capital and inflicting untold misery on city and countryside alike